The Relationship Between Pregnancy Exercise Skills And The Smoothness Of The Normal Delivery Process For Pregnancy - Lestari, Myrna; Hafsah, Hafsah; Elvieta, Elvieta; Lisni, Lisni; Akbari, Myrza (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Pregnancy exercise is a motion exercise therapy given to pregnant women to prepare themselves both physically and mentally to face and prepare for a fast, safe and spontaneous delivery. Knowledge of psychological pregnancy exercise can also help smooth delivery of pregnant women. This study aims to determine the relationship between understanding of pregnancy exercise skills and the smoothness of the normal delivery process. This study uses a quantitative approach to the type of correlational research. The population and sample in this study were mothers who had faced labor between January and June 2022 at the Syamlatira Public Health Center. The technique of dqata analysis uses Bivariate Analysis which aims to see the relationship between the Independent variable (pregnancy exercise) and the dependent variable (delivery process) by looking at the p value < 0.005. The results of the analysis using the chi-square test can be seen in table 4. Based on the results of the chi-square test analysis, the value of value = 0.000 (<0.05) means that there is a relationship between pregnancy exercise and the smoothness of the normal delivery process in pregnant women